UTILITARIANISM AND EXISTENTIAL CRISIS IN FYODOR DOSTOEVSKY’S CRIME AND PUNISHMENT (International Journal of Food and Nutritional Sciences, 2022)
This paper focuses on the principles which were hailed during 20th century, however, Dostoevsky has predicted its outcome. All the philosophies which focus objectivity fail to assist the existence. Existence is all about subjective experience. This paper deals with utilitarianism, nihilism, extraordinary man theory which is later termed by Nietzsche as Übermensch or “Beyond Man”. It also highlights the existential crisis particularly Isolation and its impacts. This paper ultimately focuses on psychological and philosophical tension in the mindscape of the protagonist Rodion Romanovich Raskolnikov. This deals with the conscience and compulsion in terms of psychology. It pictures the tussle within himself and the murder and highlights the philosophical experiments which he undertook such as Utilitarianism, Nihilism, concept of extraordinary man and his existential crisis such as isolation, depression, anxiety.